Inflectional Morphemes in Eighth Grade Students’ English Recount Writing at SMP Negeri 1 Pematangsiantar - Esra Delima Hutabarat; Bobby Pramjit Singh Dhillon; Christian Neni Purba (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to identify the types ’f inflectional morphemes used by e”ghth-grade students in writing recount texts and determine the most dominant type. A descriptive quantitative design was applied to 30 students from one eighth grade class. Data were collected through writing tests and documentation, then analyzed by identifying, classifying, and calculating the frequency of inflectional morphemes based on Yule (2020). The results show that there are seven types of inflectional morphemes used by the students: plural (-s/-es), possessive (-’s), progressive (-ing), past tense (-ed), past participle (-en/-ed), comparative (-er), and superlative (-est). The percentage of each type is as follows: plural 116 occurrences (30.4%), possessive 11 occurrences (2.93%), progressive 58 occurrences (16%), past tense 160 occurrences (45.07%), past participle 26 occurrences (4.8%), comparative 1 occurrence (0.27%), and superlative 3 occurrences (0.53%). Among these types, the past tense is the most dominant inflectional morpheme used in students’ recount writing. The findings indicate that students are generally able to express past events through their writing.